Small molecule targeting malaria merozoite surface protein-1 (MSP-1) prevent host invasion of divergent plasmodial species - Chandramohanadas, Rajesh (2014)
Malaria causes nearly 1 million deaths annually. Recent emergence of multi-drug resistance highlights the need to develop novel therapeutic interventions against human malaria. Given the involvement of sugar binding plasmodial proteins in host invasion, we set out to identify such proteins as targets of small glycans. Combining multi-disciplinary approaches, we report the discovery of a small molecule inhibitor, NIC capable of inhibiting host invasion through interacting with a major invasion-related protein, merozoite surface protein-1 (MSP-1). This interaction was validated through computational, biochemical and biophysical tools. Importantly, treatment with NIC prevented host invasion by Plasmodium falciparum and Plasmodium vivax-major causative organisms of human malaria. MSP-1, an indispensable antigen critical for invasion and suitably localized in abundance on the merozoite surface represents an ideal target for antimalarial development. The ability to target merozoite invasion proteins with specific small inhibitors opens up a new avenue to target this important pathogen.